Foreland flexure rigidity and lithospheric thickness in Eastern Cordillera and the Llanos Orientales basin from receiver functions analysis (2025)
The Colombian territory is strongly influenced by tectonic and orogenic processes that have shaped the Andean orogenic belt. This study focuses on the Eastern Cordillera (EC) and the adjacent Llanos Orientales foreland basin, where contrasting flexural lithospheric responses have been suggested. Previous research indicates that the northeastern part of the foreland lithosphere in the Llanos Orientales basin experiences significant flexure, possibly related to a reduced thickness, while in the southwestern region of the foreland basin the lithosphere is more rigid and more resistant to flexing. Using S-wave receiver function analysis (SRF’S), this project estimates the lithospheric thickness and examines the flexural response within the study area. S-to-P receiver functions were analyzed to detect the depth of the lithosphere-asthenosphere boundary (LAB) beneath several seismic stations in the Eastern Cordillera and the Llanos Orientales foreland basin. Results show LAB depths between 97 and 110 km in the southern and central EC, increasing to about 120 km near the northeastern station TAM, and depths around 105 km in the Llanos Basin. These spatial variations in LAB depth may reflect variations in the flexure of the foreland lithosphere and the amount of crustal shortening and orogenic loading along the Eastern Cordillera. Deep seismicity patterns further suggest a steeply dipping subducting slab beneath the northern EC, which may also influence the lithospheric structure. Despite limitations related to station coverage and event distribution, future studies could benefit from expanding the seismic network and increasing the dataset to improve spatial resolution and confidence in lithospheric thickness estimates.